The liminal zone - Itō, Junji, 1963-; Allen, Jocelyne, 1974- (VIZ Media, LLC, 2022)
"After abruptly departing from a train in a small town, a couple encounters a "weeping woman"--a professional mourner--sobbing inconsolably at a funeral. Mako changes afterward--she can't stop crying! In another tale, having decided to die together, a couple enters Aokigahara, the infamous suicide forest. What is the shocking otherworldly torrent that they discover there? One of horror's greatest talents, Junji Ito beckons readers to join him in an experience of ultimate terror with four transcendently terrifying tales."--Amazon.